2017
DOI: 10.1002/ajh.24818
|View full text |Cite
|
Sign up to set email alerts
|

Day 14 bone marrow examination in the management of acute myeloid leukemia

Abstract: The National Comprehensive Cancer Network (NCCN) recommends that a repeat bone marrow evaluation is carried out seven to ten days following completion of induction therapy so that if a patient's day 14 bone marrow shows residual blast cell counts of >10%, the patient would proceed early to a second cycle of induction therapy. Although blast cell counts of <5% on day 14 bone marrow is sensitive in predicting remission on day 28, various studies have found that day 14 bone marrow is highly nonspecific because a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…A blast count of < 5% on day 14 has a sensitivity of w90% to 95% for the prediction of CR at the end of treatment. 9 However, even with such high sensitivity, a 5% to 10% risk exists that a patient will have refractory disease despite hypoplastic bone marrow found on the day 14 biopsy. 16,17 In contrast, patients with a hypercellular bone marrow with > 20% blasts will usually undergo reinduction therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A blast count of < 5% on day 14 has a sensitivity of w90% to 95% for the prediction of CR at the end of treatment. 9 However, even with such high sensitivity, a 5% to 10% risk exists that a patient will have refractory disease despite hypoplastic bone marrow found on the day 14 biopsy. 16,17 In contrast, patients with a hypercellular bone marrow with > 20% blasts will usually undergo reinduction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Those with hypoplastic (< 20% cellularity and < 5% residual blasts) bone marrow will usually be monitored for count recovery. 9,10 The outcomes of patients with indeterminate day 14 bone marrow ( 20% cellularity and 5%-20% blasts) remain unclear. The decision to proceed with immediate reinduction or observation has been at the discretion of the treating physician with no defined guidance currently available.…”
Section: Introductionmentioning
confidence: 99%
“…In the current management of AML, the standing recommendation remains the pursuit of a D14BM during cytotoxic chemotherapy in order to confirm chemoablation and disappearance of leukemic blasts. If the blast count in the D14BM is >5%, the National Comprehensive Cancer Network (NCCN) recommends consideration of re-induction therapy (O'Donnell et al, 2017), but several studies have shown that this additional exposure to chemotherapy, along with the associated morbidity, is not always necessary to achieve CR (Norkin et al, 2016;Terry et al, 2017). The presence of residual blasts on the D14BM has been shown to be a sensitive predictor of achievement of CR on D28 in several studies (Liso et al, 2000;Hussein et al, 2008), but is not always highly specific (Norkin et al, 2016;Terry et al, 2017), nor always associated with OS (Hussein et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…If the blast count in the D14BM is >5%, the National Comprehensive Cancer Network (NCCN) recommends consideration of re-induction therapy (O'Donnell et al, 2017), but several studies have shown that this additional exposure to chemotherapy, along with the associated morbidity, is not always necessary to achieve CR (Norkin et al, 2016;Terry et al, 2017). The presence of residual blasts on the D14BM has been shown to be a sensitive predictor of achievement of CR on D28 in several studies (Liso et al, 2000;Hussein et al, 2008), but is not always highly specific (Norkin et al, 2016;Terry et al, 2017), nor always associated with OS (Hussein et al, 2008). Specifically, one study illustrated the limitations of the D14BM by showing that 36% of the AML patient cohort who had residual blasts on their D14BM achieved CR or CR with incomplete count recovery without additional chemotherapy (Norkin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation